Faktor-Faktor yang memengaruhi Akuntabilitas Kinerja Instansi Pemerintah (Studi empiris pada OPD di Pemerintah Provinsi Banten) - Zulfiandri, Andri (JURNAL RISET AKUNTANSI TIRTAYASA, 2017)
This study was to examine the budget goal clarity, competence of personnel, implementation of local financial accounting and quality control of financial statements to the accountability of the performance of government agencies. The population in this study were 44 OPD in the Government of Banten Province by sampling using purposive sampling with the number of respondents as many as 80 respondents. Data was analyzed using SmartPLS version 3.0 Professional. The results of this study stated that the budget goal clarity, competence of personnel, implementation of local financial accounting and financial reporting quality control affect the performance accountability of government agencies. Results of this research is also expected to provide input to OPD to further improve performance accountability of government agencies. For further research in order to add the variable management commitment, leadership style and organizational culture.Keywords : Budget Targets Clarity, Competence of Administrative, Accounting Application Regions Financial, Financial Reports Quality Control, Accountability Government Performance.